Hoveyda-Grubbs type metathesis catalyst immobilized on mesoporous molecular sieves MCM-41 and SBA-15 - Balcar, Hynek; Shinde, Tushar; Zilková, Naděžda; Bastl, Zdeněk (Beilstein journal of organic chemistry, 2011)
A commercially available Hoveyda-Grubbs type catalyst (RC303 Zhannan Pharma) was immobilized on mesoporous molecular sieves MCM-41 and on SBA-15 by direct interaction with the sieve wall surface. The immobilized catalysts exhibited high activity and nearly 100% selectivity in several types of alkene metathesis reactions. Ru leaching was found to depend on the substrate and solvent used (the lowest leaching was found for ring-closing metathesis of 1,7-octadiene in cyclohexane - 0.04% of catalyst Ru content). Results of XPS, UV-vis and NMR spectroscopy showed that at least 76% of the Ru content was bound to the support surface non-covalently and could be removed from the catalyst by washing with THF.
Keywords: hybrid catalysts; alkene metathesis; catalyst immobilization; mesoporous molecular sieves; Ru–alkylidene complexes